The Diaryliodonium(III) Salts Reaction With Free-Radicals Enables One-Pot Double Arylation of Naphthols - Satkar, Yuvraj; Wrobel, Kazimierz; Trujillo-González, Daniel E.; Ortiz-Alvarado, Rafael; Jiménez-Halla, J. Oscar C.; Solorio-Alvarado, César R. (Frontiers in Chemistry, 2020)
The chemoselective reaction of the C- followed by the O-centered naphthyl radicals with the more electron-deficient hypervalent bond of the diaryliodonium(III) salts is described. This discovered reactivity constitutes a new activation mode of the diaryliodonium(III) salts which enabled a one-pot doubly arylation of naphthols through the sequential Csp2-Csp2/O-Csp2 bond formation. The naphthyl radicals were generated in the reaction by the tetramethylpiperidinyl radical (TMP·) which resulted from the homolytic fragmentation of the precursor TMP2O. Experimental and DFT calculations provided a complete panorama of the reaction mechanism.